2005
DOI: 10.1111/j.1744-9987.2005.00276.x
|View full text |Cite
|
Sign up to set email alerts
|

Rheopheresis in Patients with Critical Limb Ischemia––Results of an Open Label Prospective Pilot Trial

Abstract: Rheopheresis is a specifically designed application of double filtration plasmapheresis, for extracorporeal treatment of microcirculatory disorders. Safety and efficacy of Rheopheresis for wound healing and skin oxygenation were investigated in patients with critical limb ischemia. Twelve patients of Fontaine stage III-IV were treated with a series of 10 Rheopheresis sessions over 17 weeks. Transcutaneous oxygen pressure (tcpO(2)) and ankle-brachial index (ABI) were repeatedly determined to monitor the effects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
20
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 23 publications
3
20
0
Order By: Relevance
“…In the treatment group, the mean reduction rates achieved were: for LDL 64.9% (s=0.09), for alpha-2-macroglobulin 52.5% (s=0.15) and for fibrinogen 59.6% (s=0.12), demonstrating an efficient reduction of hemorheological parameters which is in accord to already published data [10,11].…”
Section: Efficacysupporting
confidence: 90%
See 2 more Smart Citations
“…In the treatment group, the mean reduction rates achieved were: for LDL 64.9% (s=0.09), for alpha-2-macroglobulin 52.5% (s=0.15) and for fibrinogen 59.6% (s=0.12), demonstrating an efficient reduction of hemorheological parameters which is in accord to already published data [10,11].…”
Section: Efficacysupporting
confidence: 90%
“…A systematic decrease in choroidal circulatory parameters was observed in combination with an increase in the severity of AMD features associated with risk for the development of choroidal neovascularisations (CNV), supporting the role of ischemia in the development of CNV [26]. Rheopheresis has been demonstrated to increase oxygen concentration in ischemic tissues [10,11]. Improvement of the pulsatile ocular blood flow and shortening of the arteriovenous passage time in patients with AMD after Rheopheresis treatment demonstrated a positive effect of Rheopheresis on the microcirculation directly in the eye [27,28].…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Moreover, ABI is more relevant in studies of medium caliber vessels than of the microcirculation, which is theoretically more sensitive to variations of plasma viscosity. In other studies conducted with other apheretic methods (rheopheresis), ABI showed no significant improvements either [31] .…”
Section: Discussionmentioning
confidence: 98%
“…In fact, a reduction in fibrinogen using nonselective methods for this substance such as LDL apheresis [30] or rheopheresis [31] resulted in increased muscle oxygen tension and transcutaneous oxygen pressure, improving the symptoms in both cases. Our study confirms these findings, emphasizing the value of fibrinogen reduction in rapidly improving the clinical symptoms, likely induced by correction of the rheological properties of blood.…”
Section: Discussionmentioning
confidence: 99%